Is There a Cigarette Catch-Up Effect for Biracial Black Youth?. Issue 4 (4th July 2019) - Clark Goings, Trenette; Teran Hidalgo, Sebastian J.; Gilreath, Tamika D.
Abstract: Introduction : The catch-up effect is a phenomenon in which the tobacco-use prevalence rates of White individuals are initially greater than the rates of Black individuals, but by the time the youth enter young adulthood, the prevalence rates for Black individuals catch up to or exceed the cigarette-use rates of White individuals. We test the catch-up effect by comparing the cigarette trajectories of monoracial and biracial Black adolescents with the trajectories of White adolecents. Methods : We used longitudinal data from the National Longitudinal Study of Adolescent and Adult Health. Our sample includes 9421 respondents. Study hypotheses are tested using latent growth curve modeling. Results : Findings revealed a catch-up effect for two of four outcomes. The catch-up effect was observed most often for Black individuals. Black and Black-Hispanic individuals showed cigarette smoking patterns consisted of a catch-up effect while Black-American individuals showed smoking patterns consisted of a cross-over effect. Black and Black-American Indian individuals showed a stark contrast to the typical bell-shaped curve with substance use patterns demonstrating upward slope trajectories. Conclusions : Interventions to prevent and reduce tobacco use in these populations are warranted.